ELECTORAL DISPUTES AND NIGERIA’S FEDERALISM (1999 – 2023) (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
The study examined the effects of electoral disputes on Nigeria’s federalism. The activities of the electoral system have created out comes that has led to litany of disputes in every election circle. This dispute tear at the very heart of multi-level governance in Nigeria as Nigeria is essentially a federal state. Content analysis was used to gather data for the study. Findings from the study reveal that from the advent of the country’s fourth republic in 1999 disputes have arisen as a result of dissatisfaction with the conduct of elections and this has impacted negatively on the country’s federalism. The study recommends institutionalization of structures that will guarantee free and fair elections. The study concludes by observing that election seasons have further polarized Nigeria affecting the practice of federalism in the country. Therefore, there is the need to put mechanisms in place to checkmate the manipulation of Nigeria’s fault lines for electoral purposes by politicians due to its negative impact on the country’s federalism.